Telemedicine in Palliative Care: Implementation of New Technologies to Overcome Structural Challenges in the Care of Neurological Patients - Weck, Christiane Eva; Lex, Katharina Maria; Lorenzl, Stefan (Frontiers in Neurology, 2019)
Telemedicine provides a possibility to deal with the scarcity of resources and money in the health care system. Growing necessity in palliative care has been found for patients with neurodegenerative disorders. Either the palliative or the neurological expertise is often missing in caring of these patients. Since palliative care means a multidisciplinary approach it is meaningful to use palliative care structures as a basis. There exists no systematic access to neurological expertise in an outpatient setting. A successful link of two existing resources is shown in this project connecting the Department of Neurology of a University Hospital with specialized outpatient palliative care (SPC) teams. A videocounselling system is used to provide expert care for neurological outpatients in a palliative setting. Methods: A prospective explorative single arm pilot trial was implemented to provide a mobile telesystem for 5 SPC teams. The opportunity was given to consult an expert in neuropalliative care at the specialized centre in the hospital (24/7). Semistructured interviews were held with the physician of the SPC teams after a trial duration of 9 months. Results: Our data provides strong evidence that the technical structure applied in this project allows a reasonable neurological examination at distance. Qualitative interviews indicate a major impact on the quality of work for the SPC teams and on the quality of care for neurological patients. Conclusion: The system proves to be useful and is well accepted by caregivers and patients. It supplies a structure that can be transported to other disciplines.